Mitochondrial ROS promote macrophage pyroptosis by inducing GSDMD oxidation - Wang, Yufang (J Mol Cell Biol, 2019)
Disrupted mitochondrial membrane potential (MMP) and reactive oxygen species (ROS) generation are often associated with macrophage pyroptosis. It remains unclear how these forms of mitochondrial dysfunction relate to inflammasome activation and gasdermin-D (Gsdmd) cleavage, two central steps of the pyroptotic process. Here, we also found MMP collapse and ROS generation induced by Nlrp3 inflammasome activation as previous studies reported. The elimination of ROS alleviated the cleavage of Gsdmd, suggesting that Gsdmd cleavage occurs downstream of ROS release. Consistent with this result, hydrogen peroxide treatment augmented the cleavage of Gsdmd by caspase-1. Indeed, four amino acid residues of Gsdmd were oxidized under oxidative stress in macrophages. The efficiency of Gsdmd cleavage by inflammatory caspase-1 was dramatically reduced when oxidative modification was blocked by mutation of these amino acid residues. These results demonstrate that Gsdmd oxidation serves as a de novo mechanism by which mitochondrial ROS promote Nlrp3 inflammasome-dependent pyroptotic cell death.